A revision of “crowned” Daphnia (Ctenodaphnia) atkinsoni species group (Cladocera: Daphniidae) combining morphological and genomic evidence - Garibian, Petr G.; Pereboev, Dmitry D.; Karabanov, Dmitry P.; Galimov, Yan R.; Petrusek, Adam; Kotov, Alexey A. (Zootaxa, 2026)
The cladoceran subgenus Daphnia (Ctenodaphnia) Dybowski & Grochowski, 1895 (Cladocera: Anomopoda: Daphniidae), particularly diverse in temporary waters of temperate regions, contains several species groups with distinct morphologies. Among these, populations with a “head plate”, a prominent anterior median projection of the carapace to the head shield, have been described multiple times since the mid-19th century. In our previous paper, we have demonstrated that the “crowned” Eurasian daphniids, the head plate of which may be flanked with conspicuous thorns, represent two strongly divergent clades separated tens of millions years ago that are not in a sister-group relationship: D. (C.) triquetra Sars, 1903 and D. (C.) atkinsoni group. Here, we focus on a detailed final revision of the atkinsoni group based on morphology, mitochondrial and whole-genome phylogenies. Both molecular (including genomic) and morphological analyses of available samples confirmed existence of three species: D. (C.) atkinsoni Baird, 1859 s. str. nomen protectum, D. (C.) ulomskyi Behning, 1941, and D. (C.) nuda Keiser, 1931. The overall diversity of the group may be higher, e.g., as a fourth genetic lineage was reported from Hungary. As we had no material for its revision, its taxonomic status needs to be checked in the future. The three studied species are redescribed in detail. They mainly differ in the adult male morphology, while their parthenogenetic females are similar. Our pessimistic conclusion is that the taxonomy based solely on morphological characters is already reaching the limits of its resolution in intensively studied cladoceran taxa such as Daphnia (Ctenodaphnia), following the fate of D. (Daphnia) morphological taxonomy. Only a few, and very minute, morphological differences support the discrimination of taxa described above.